The Study of “Social Governance” As a Managerial Activity in the Sociology of Governance (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
When it is called socially management, the form of social relations established between people in relation to power and subordination is understood, which is determined by the location and tasks of people in a labor organization. To date, in sociology, the definition of management as “directing the behavior of people in a certain way based on the interests of the organization without noticing them” is widely used. Therefore, sometimes scientists equate management to art.In this article, “Social Management” has been scientifically researched as a specific type of management activity.